Assessment of Stress Tolerance, Productivity, and Forage Quality in T1 Transgenic Alfalfa Co-overexpressing ZxNHX and ZxVP1-1 from Zygophyllum xanthoxylum - Kang, Peng; Bao, Ai-Ke; Kumar, Tanweer; Pan, Ya-Qing; Bao, Zhulatai; Wang, Fei; Wang, Suo-Min (Frontiers in Plant Science, 2016)
Salinization, desertification, and soil nutrient deprivation are threatening the production of alfalfa (Medicago sativa L.) in northern China. We have previously generated T0 transgenic alfalfa co-overexpressing Zygophyllum xanthoxylum ZxNHX and ZxVP1-1 genes with enhanced salt and drought tolerance. To further develop this excellent breeding material into the new forage cultivar, stress tolerance, productivity, and forage quality of T1 transgenic alfalfa (GM) were assessed in this study. The GM inherited the traits of salt and drought tolerance from T0 generation. Most importantly, co-overexpression of ZxNHX and ZxVP1-1 enhanced the tolerance to Pi deficiency in GM, which was associated with more Pi accumulation in plants. Meanwhile, T1 transgenic alfalfa developed a larger root system with increased root size, root dry weight and root/shoot ratio, which may be one important reason for the improvement of phosphorus nutrition and high biomass accumulation in GM under various conditions. GM also accumulated more crude protein, crude fibre, crude fat, and crude ash than wild-type (WT) plants, especially under stress conditions and in the field. More interestingly, the crude fat contents sharply dropped in WT (by 66%-74%), whereas showed no change or decreased less in GM, when subjected to salinity, drought or low-Pi. Our results indicate that T1 transgenic alfalfa co-overexpressing ZxNHX and ZxVP1-1 shows stronger stress tolerance, higher productivity and better forage quality. This study provides a solid foundation for creating the alfalfa cultivars with high yield, good quality and wide adaptability on saline, dry and nutrient-deprived marginal lands of northern China.